Objective acoustical methods in phoniatric diagnostics of speech organ disorders - Janusz KACPROWSKI (Archives of Acoustics, 2016)
Physical parameters of the speech signal contain essential information on the anatomical structure and the kinematics of the biological sound source, i.e. the human speech organ. Several objective acoustical methods have been proposed and developed recently, which not only assist, but in some cases are even superior to the classical, mostly intrusive and/or subjective diagnostic methods, commonly used at present in clinical practice in laryngology and phoniatrics. The subject of the present paper is the theoretical fundamentals and the engineering performance of some selected methods and systems for speech signal processing and analysis, aimed at acoustical diagnosis of larynx and vocal tract pathology. The current status of fundamental research in this domain is briefly reviewed and discussed, including the scientific activity and achievements of the Department of Cybernetic Acoustics, IFTR–PAS. Preliminary results of experimental research are given. Special attention is paid to the role of model investigations in the development of acoustical diagnostic methods and systems in laryngology and phoniatrics. The references play a role of the reader's guide throughout the rather scarce literature on the subject considered.